Pengaruh ABC Classification, Inventory Tracking Technology, dan Order Fulfillment Speed Terhadap Efektivitas Pengendalian Persediaan - M. Ilham Syahrul Qur’ani; Adiatma Zefanya Loppies; Jilan Azzahra Salsabila; Supriatun Supriatun; Enisa Tunggal Dewi; Maria Yovita R. Pandin; Hwihanus Hwihanus (Economic Reviews Journal, 2026)
This study aims to analyze the influence of ABC Classification, Inventory Tracking Technology, and Order Fulfillment Speed on the effectiveness of inventory control. The research is motivated by recurring issues of overstock, stockout, and stock record inaccuracies that reduce operational efficiency, increase storage costs, and lower service levels. A Systematic Literature Review (SLR) was conducted using 10 relevant articles published between 2020–2025, with thematic synthesis employed to identify consistent empirical findings. The results show that ABC Classification enhances inventory control effectiveness by prioritizing high-value items, improving picking accuracy, and reducing operational bottlenecks. Inventory Tracking Technology significantly increases stock accuracy, visibility, and reduces stockout risks while lowering holding costs through real-time monitoring. Meanwhile, Order Fulfillment Speed improves inventory turnover, maintains service levels, decreases lead time, and prevents excessive stock accumulation. Collectively, these three variables form a more responsive, efficient, and accurate inventory control system. The study contributes theoretically by strengthening evidence on the integration of classification methods, tracking technologies, and fulfillment strategies in inventory management. Practically, it recommends implementing digital tracking systems, applying ABC prioritization, and improving fulfillment speed to optimize inventory control across industries.